Проблемна ситуація в стратиграфії палеоліту України - Гладких, М.І. (Археологія і давня історія України, 2011)
Публікація присвячена аналізу сучасного стану
вивчення стратиграфії палеоліту України. Публикация посвящена анализу современного
состояния изучения стратиграфии палеолита Украины. The paper proposes correlation of quaternary stratigraphye
subdivisions for different geographical zones,
represented by several researchers. These sources give
contradictory picture of the historical process in Paleolithic
time of Ukraine.